Melastomaceae sp: a new potential of antioxidant agent / Ropisah Me ... [et al.] - Me, Ropisah; Wan Mohd Samsudin, Wan Nur Aqilah; Hasan, Nur Syakilla Asyiqin; Hasan, Nur Syaida Maisarah (Faculty of Computer and Mathematical Sciences, 2022)
Melastomaceae species such as Melastoma Malabathricum and Dissochaeta Gracilis are belongs to Melastomataceae family which are found mostly in the tropics and contains bioactive compounds to treat various illness. The purpose of this study was carried out to investigate the presence of phytochemical groups and antioxidant activity of the leaves of M. malabathricum and D. gracilis. For this study, the plant sample undergoes extraction processes using three difference polarity of solvents which are hexane, ethyl acetate and methanol by cool extraction method. The highest yield percentage is methanol leaves extract for both samples. The phytochemical analysis study also revealed that many secondary metabolites presence inside M. malabathricum and D. gracilis such as steroids, flavonoids and terpenoids but absence of alkaloids compounds. Meanwhile, both samples have shown the presence of tannins, saponins and phenols compound for ethyl acetate and methanol crude extracts but not in hexane crude extract. The present of flavonoids and phenolic compound showed their potent antioxidant property so they could be the rich source of natural antioxidants. The methanol extract of D. gracilis (54.24 µg/mL) significantly lower of DPPH radical scavenging activity IC50 which indicate better antioxidant properties as compared to the methanol extract of M. malabathricum (111.90). As conclusion, this study discovered that M. malabathricum and D. gracilis leaves could be assigned as natural antioxidant and its open door for the bioactive compound identification in the field of pharmaceutical research.